Peran Komunikasi Pemasaran Dalam Membangun Brand Awareness UMKM - Supit, Gerry Rizky Andrean (STISIP Widyapuri Mandiri Sukabumi, 2025)
For micro, small, and medium enterprises (MSMEs), marketing communication plays a strategic role in increasing their brand awareness. In today's internet era, effective marketing strategies, such as the use of social media, digital advertising, and promotional strategies, are essential to increasing MSME visibility. The purpose of this study was to analyze how marketing communication impacts MSME brand awareness. This study used a quantitative method, with questionnaires distributed to 200 MSME actors and customers in the culinary, fashion, and service industries. Data were analyzed using linear regression and descriptive statistics to determine the relationship between marketing communication variables (digital advertising, social media promotion, and advertising) with the level of MSME brand awareness. The results showed that there was a positive and significant influence between marketing communication and MSME brand awareness (p <0.05). With a contribution of 65% to increasing brand awareness, social media is the most effective communication channel. In addition, interesting marketing content and customer interaction increase customer loyalty and increase MSME competitiveness in the market. The results indicate that MSMEs must regularly optimize their digital marketing communication strategies to increase brand awareness.